مسؤولية القائم بالإدارة في شركة المساهمة - البار رميساء, رميساء; بن ثامر شهلة, شهلة; مشحاط خرفية, خرفية (University of Eloued جامعة الوادي, 2023)
تأتي ىاتو الد ا رسة مكممة لغيرىا مف الد ا رسات السابقة المتعمقة بمسؤولية القائ بالإدارة في شركات المساىمة، التي تعد النموذج أمثؿ لشركات الامواؿ نظ ا ر لأىميتيا فًي تنمية الاقتصاد، ولكونيا تستقطب رؤوس أمواؿ ضخمة وتختص بالمشاريع الكبرى. وقد تطرقنا في ىذه الد ا رسة إلى المسؤولية المدنية التي يتحمميا المسير عند مخالفتو للالت ا زمات القانونية المفروضة عميو سواء كانت تمؾ الالت ا زمات محددة في النصوص التشريعية والتنظيمية المعموؿ بيا في مجاؿ الشركات، وكذلؾ يمكف اف يتعرض المسير لممساءلة الج ا زئية عف افعالو الشخصية في الشركة س واء كانت نتيجة خطأ عمدي او غير عمدي، فيعد المسير فاعلا أساسيا في حالة ارتكابو الفعؿ المجر بمفرده سواء كانت الفعؿ قانوني او غير قانوني اما في حالة ارتكابو لمجريمة عف طريؽ المساىمة او التواطؤ فإنو يعد فاعلا ثانويا او شريكا في الجريمة. وقد قا المشرع الج ا زئري بسف عقوبات لمحد مف ىكذا تصرفات التًي قد تتسبب في الاض ا رر بالمسير أو ب أ رس ماؿ الشركة، لتنظ مسؤولية المسير المدنية والج ا زئية ونحف نطمح أف تكوف د ا رستنا اسياما قيمنا يت اضافتو إلى مجموعة الد ا رسات المتعمقة بموضوع الشركات التجارية.This study complements other previous studies on the administrator's responsibility in shareholding companies, which are the ideal model for financial companies because of their importance in the development of the economy, and because they attract large capital and specialize in major enterprises. In this study, we have addressed the civil liability of the walker in breach of the legal obligations imposed on him, whether those obligations are defined in the applicable legislative and regulatory texts in the field of companies.as well as being liable to criminal liability for his personal actions in the company, whether as a result of intentional or unintentional error, A person who commits an offence alone, whether lawful or unlawful, or who commits the offence through contribution or complicity, is a minor or accomplice to the offence. The Algerian legislature has enacted sanctions to limit such actions, which may cause damage to the course of action or to the company's capital, to regulate civil and criminal liability. We hope that our study will be a valuable contribution to the collection of studies on the subject of commercial companies.
م .ق.إ
Keywords: المسؤولية القائ بالإدارة شركة المساىمة; Responsibility-charge d'affaires-Joint Stock Company